Investigation of Cultural Values in English Textbooks for Junior High School Students - Sri Arfani; Juhana Juhana; Hanna Sundari; Wisma Yunita (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to identify the embodiment of cultural values in English textbooks for junior high school students. This research used a qualitative approach with a content analysis method. The research data was in the form of a collection of discourse texts in the form of monologues, dialogues and exercises. The data were taken from two books entitled Scaffolding and In Focus, published by the Book Center of the Ministry of National Education. It is grade X. The data analysis procedure used in this research was qualitative content analysis. The process of validity was done through credibility, transferability, triangulation, dependability, and confirmability. The results showed that the dominant cultural value was the optimistic value of 43%. Then followed by the brotherhood value of 23.80%, the social value of 19% and the freedom value of 14%. Each cultural value found also describes some more specific values. The value of freedom contains character values, namely the value of independence and hard work. The value of brotherhood contains character values, namely friendliness and responsible; the optimistic value contains character values, namely courage, creativity, discipline, and curiosity, and social values contain character values, namely cooperation. This study concluded that English textbooks had the important value of increasing students’ character as cultural values.